Learning Methods and Approaches in Islamic Educational Traditions - Intan Permata Sari; Muhtadi Abdul Mun’im (Penerbit Hellow Pustaka, 2026)
This study aims to describe and analyze learning methods and approaches within the Islamic educational tradition, and to assess their relevance in the contemporary educational context. Since its inception, Islamic education has developed learning methods that emphasize the integration of knowledge, morality, and spirituality, as seen through the practices of tahfizh (memorization of the Qur'an), talaqqi (recitation of the Qur'an), question and answer (Q&A), value instillation, and teacher role models. However, previous studies have tended to discuss traditional methods and modern approaches separately, thus lacking a comprehensive understanding of their relationship and integration. Through library research, data were obtained from accredited national journals, scientific books, and relevant academic sources, then analyzed using a qualitative descriptive approach. The research results show that Islamic learning methods are dynamic and continuously evolving, characterized by the integration of classical methods and modern pedagogical approaches such as Contextual Teaching and Learning (CTL), Problem-Based Learning (PBL), and humanistic learning. The role of teachers as role models (uswah) and facilitators is also a crucial factor in the successful internalization of values and character formation of students. This research confirms that the combination of classical and modern methods can produce an Islamic learning model that is holistic, contextual, and adaptive to the challenges of 21st-century education.